Corak Ijtihad Syi’ah Imamiyah Pasca Kegaiban Imam Mahdi - Bisri, H.Hasan (TAJDID, 2016)
In the doctrine of Shi’te eschatology (a branch of theology), Mahdi Imam and he is also called twelfth Imam being disappeared (ghoybah) will reappear in the last day of the world and from the Devine government to realize the justice, piece and welfare of mankind. The belief of Mahdi Imam has helped the Shi’tes with great patience to face a bad situation during the history of social political unrest in the numerous parts of Islamic world. The doctrine of ghaybah is a direct consequence of belief that the world will not secure if it is without being led by an Imam (leader) to guide mankind through the straight way. During the virtual disappearance of twelfth Imam, the political and religious duties are under the leadership of Ulama (Islamic scholars) reaching the level of Mujtahid-an expert in Islamic law (marja’ taklid/source of authority) acts as representative of the public. Since the twelfth Imam has disappeared, shi’te ulama have completely different opinions in the authority of ijtihad and the relationship with political structure, so the conflict arises between Akhbari group and Ushuli group and this is finally won by Ushuli group. The methods of ijtihad (original interpretation of problems not precisely covered in the Qur’an and hadith) used by Ushuli group are clear thinking and contemplation of the verses of Qur’an and hadith containing general principles to be interpreted to solve juridical problems that come out in society.